Correlations between negative life events and suicidal ideation among Chinese adolescents: a meta-analysis - He, Xubin; Yang, Ping; Yu, Qinyao; Yang, Bo (Frontiers in Psychiatry, 2023)
Background: suicide ideation (SI) has become a serious social issue worldwide, and research has found a certain correlation between Negative Life Events (NLE) and SI. Nevertheless, this relationship is still not clear among Chinese adolescents, a special population. Hence, this investigation performed a meta-analysis of observational research on the correlation between NLE and SI among adolescents in China, to further clarify the association.We performed an extensive search on seven electronic databases starting from their establishment until March 10, 2023. The research mainly focused on cross-sectional studies conducted on samples of Chinese adolescents. To examine the association between NLE and SI, a meta-analysis model using random effects was utilized. To investigate moderating factors such as age, region, assessment tools for SI, and year of publication, subgroup and meta-regression analyses were performed. The AHRQ evaluated the quality of the study. The synthesis of data was conducted utilizing STATA software (version 16).Results: Ultimately, a total of 30 cross-sectional studies were selected for this analysis, including 39,602 individuals in the participant sample. The results showed that NLE was moderately positively correlated with SI among Chinese adolescents (r = 0.29, 95% CI: 0.26, 0.32). In addition, this relationship was moderated by regional differences and the measurement tool used for SI. Studies conducted in Western China showed a higher correlation coefficient than those conducted in Eastern and Central China. Moreover, research conducted with the SSIOSS demonstrated a stronger correlation coefficient compared to studies utilizing the BSI-CV or other assessment instruments. This is a provisional file, not the final typeset article Conclusion: This meta-analysis indicates that NLE is linked to SI in Chinese teenagers, especially those residing in Western regions of China. Identifying and intervening in NLE and associated risk factors are crucial to prevent suicide within this demographic.